2010
DOI: 10.1039/c0cc01058h
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i) complex of N,N′-disubstituted cyclic thiourea with in vitro and in vivo anticancer properties—potent tight-binding inhibition of thioredoxin reductase

Abstract: Coinage metal complexes of an N,N'-disubstituted cyclic thiourea exert significant cytotoxicities to cancer cells and, in particular, the gold(i) thiourea complex exhibits a potent tight-binding inhibition of the anticancer drug target thioredoxin reductase with an inhibitory constant at nanomolar level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 44 publications
2
74
0
Order By: Relevance
“…12 As reported, it was shown that increasing steric bulk in the ortho position of the aniline led to more challenging reaction conditions. 1f required heating at reflux for 3 days, and was isolated in a low yield (23%), and 1h could not be formed even after 1 week heating at reflux.…”
mentioning
confidence: 96%
“…12 As reported, it was shown that increasing steric bulk in the ortho position of the aniline led to more challenging reaction conditions. 1f required heating at reflux for 3 days, and was isolated in a low yield (23%), and 1h could not be formed even after 1 week heating at reflux.…”
mentioning
confidence: 96%
“…Che et al have shown that bis-thiolate derived Au(I) complexes can be attained through the use of thiourea (TU) [24]. …”
Section: Anticancer Study Of Au(i) Complexesmentioning
confidence: 99%
“…The precursor ligands featured in complexes 1 and 2 were obtained after esterification of the corresponding amino acids 7 and 8 to their α-amino esters 11 followed by triflation of the primary amine with triflic anhydride ( Fig. 2).…”
Section: Modification Of the X Ligandmentioning
confidence: 99%
“…The L-ligands can be phosphines, N-heterocyclic carbenes (NHCs) or sulfides, whereas the X-ligands range from thiolates, featured notably in the anti-rheumatoid auranofin, bis-triflic amide, chlorides, alkoxides, sulfonates and NHCs. [5][6][7][8][9][10][11][12][13] Previously the structural nature of ligands L and X limited their potential for derivatization and the corresponding complexes exhibited significant cytotoxicity. We have developed two complementary approaches that combine biocompatible ligands with tunable lipophilic groups to provide a platform for anti-cancer drug discovery.…”
Section: Introductionmentioning
confidence: 99%